How to Improve the Propensity to Indebtedness of Shopee Paylater Gen Z Users? - Arief Iswariyadi; Florentina Kurniasari; Hendy Tannady; Muhamad Aslan Kazhim (Arkus, 2023)
Paylater payment methods in Indonesia can be financially harmful to society, especially the many cases of users, especially young people, who fail to pay their paylater. This research aimed to find the relationship between financial literacy, materialism, and compulsive buying to a propensity to indebtedness in Shopee gen-Z users. This study is casual research using a quantitative approach and is described descriptively. This study uses the population of generation Z Shopee Paylater users in Jabodetabek. The sample used was 170 generation Z Shopee Paylater users in Jabodetabek. Data was collected through a questionnaire. The analysis model used in this research is structural equation modeling (SEM). The results of the research that has been done state that there is an insignificant influence between financial literacy and propensity to indebtedness. Other results show a positive impact between materialism on the propensity to indebtedness, compulsive buying on propensity to indebtedness, and materialism on compulsive buying. In conclusion, financial literacy has a negative impact on materialism and compulsive buying.